The Determination of Tannin Content and Larvicidal Activity Test Of Ripe Sapodilla Fruit Peel (Manilkara zapota) - Trisnawati, Ade; Sri Wahyuningsih; Febriyandhi Yahya (International Journal of Multidisciplinary Sciences and Arts, 2023)
This study aimed to determine the results of total tannin content determination of sapodilla peel extract (Manilkara zapota) and the effectiveness of sapodilla peel extract (Manilkara zapota) as a Aedes aegypti mosquito larvicide. The method used was a quantitative descriptive with a purposive sampling method. The sample was ripe sapodilla (Manilkara zapota) peel. The determination of tannin content in sample extracts was analyzed using UV-Vis spectrophotometry. The extraction of tannins from sapodilla peel (Manilkara zapota) was carried out by maceration method using 70 % ethanol. Based on the research results it was found that the total content of sapodilla peel extract was 3,058 mg GAE/g extract. The results of the larvicide test showed that the sapodilla peel extract could be used as an Aedes aegypti larvicide with the most effective concentration in killing 50% of the larvae at a concentration of 20,000 ppm.